Analysis of Maternal Characteristics, Knowledge, and Attitude Factors Associated with the Coverage of K6 Antenatal Visits at Parung Panjang Health Center - Susanti Susanti; Yeny Sulistyowati; Zarfiel Tahal; Ismail Sangadji (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Antenatal care (ANC) is a critical component of maternal health services aimed at improving maternal outcomes and reducing the risk of pregnancy-related complications. The Indonesian government has established a minimum standard of six antenatal visits (K6) to ensure optimal monitoring of pregnancy. However, the coverage of K6 visits at the primary healthcare level has not fully met the expected targets. Maternal characteristics, including demographic and behavioral factors, are considered important determinants influencing adherence to antenatal visits. Objective: This study aimed to analyze maternal characteristics, knowledge, and attitudes, as well as their association with the coverage of K6 antenatal visits in the working area of Parung Panjang Health Center in 2025. Methods: This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 154 pregnant women selected using a total sampling technique. The dependent variable was K6 antenatal visit coverage (complete vs. incomplete). Independent variables included maternal age, educational level, employment status, parity, level of knowledge, and attitudes toward antenatal care. Data were collected using a structured questionnaire and verified through antenatal visit records in the Maternal and Child Health (MCH) handbook. Data analysis was conducted using univariate analysis to describe respondent characteristics, bivariate analysis with chi-square tests, and multivariate analysis using multiple logistic regression with a significance level of 5%. Results: More than half of the respondents (53.9%) had not completed the recommended K6 antenatal visits. Univariate analysis showed that the majority of mothers had low educational attainment and insufficient levels of knowledge and supportive attitudes toward antenatal care. Bivariate analysis revealed that maternal education, knowledge, and attitudes were significantly associated with K6 visit coverage (p<0.05). Multivariate analysis indicated that maternal attitude was the most dominant factor associated with complete K6 visits after controlling for other maternal characteristics. Conclusion: The coverage of K6 antenatal visits in the study area remains low and is influenced by maternal characteristics, particularly education, knowledge, and attitude. Maternal attitude is the dominant factor associated with the completeness of K6 antenatal visits. Strengthening health education and fostering positive attitudes toward antenatal care services need to be enhanced to improve pregnant women’s adherence to antenatal visits